Aplikasi Sistem Informasi Geografis (Gis) Untuk Pemetaan Sebaran Burung Air Pada Kawasan Konservasi Pulau Pombo Kabupaten Maluku Tengah - Wakano, Deli; Sahertian, D. E.; Seumahu, C. A.; Ukratalo, A. (Biosel Biology Science and Education, 2022)
The conservation area of Pombo Island is the path of migratory shorebirds. Nowadays, the rate of damage to forest and coastal ecosystems in the conservation area of Pombo Island is thought to have an effect on the presence of water birds. This study aims to map the distribution of waterbirds on Pombo Island, Central Maluku Regency. This study uses a combination method between the point count method (Point Count). The distance used in this study was 20 m. The time period for counting the number of individual birds at each counting point is set at 10 minutes. Transfers between counting points, which are 20 m apart, take about 30 minutes. The coordinates of each bird watching point were recorded using a GPS tool to determine the geographic distribution of waterbirds in the conservation area of Pombo Island. Furthermore, the results of the coordinates of the GPS device are used to map waterbirds in the studied locations. The results obtained were four species of water birds, namely the Coast Trinil (Actitis hypoleucos), Swamp Trinil (Tringa stagnatilis), Bush Trinil (Tringa glareola) and Little Egret (Egretta garzetta) with random distribution patterns. Keywords: Waterbirds, GIS, Distribution, Conservation area, Pombo Island